The marginalised in post-independence Zimbabwe in selected stories in Memory Chirere’s short story anthology Somewhere in this country (Journal for Studies in Humanities and Social Sciences, 2015)
Memory Chirere is one of the contemporary Zimbabwean writers who uses the short story genre as a mode of expression. In his fi rst collection of short stories in English under one book, Somewhere in this Country (2006), Chirere focuses on the marginalised members of society in their day-to-day struggles for survival in post-independence Zimbabwe. Zimbabwe’s masses leading miserable lives, years after independence which was obtained in 1980, refl ects that the black leaders failed to fulfi ll their erstwhile promises of better days to the majority. At the centre of each of the stories selected to be studied in this article, “Suburb”, “An Old Man”, “Maize” and “Sitting Carelessly” is the writer’s touching compassion for the underprivileged members of society such as squatters, street kids, land-hungry peasants and displaced farm workers respectively. However, in “Maize” the black government is applauded for alleviating the situation of peasants by giving them land under the recent land reform programme. Hence, notable in Chirere’s criticism of society and its institutions is his objectivity.